Enhanced Converter Control using PR Controller in Electric Springs - P.Srinivasarao; M.R.Mohamed; K.K. Deepika; D.J K Kishore; A. Anjaneyulu (Utilitas Mathematica, 2025)
Electric Spring is the recent paradigm in demand-side management to control the load demand following the generation. This paper details a diagnostic approach to the design of a Proportional Resonant (PR) controller for a singlephase grid-connected system with an Electric Spring (ES) with Back-to-Back Converter. Design is ensured using bode diagrams for various PR controller parameters. Also, the design of the DC-link voltage control loop is detailed. Fourier analysis is demonstrated to measure ripple content in a grid. Simulation results of Electric Spring with PR controller confirm the ability of ES to track reference power for fixed and variations in reference power, and dynamic load changes.